Application of CUDA for parallelization three-dimensional problem of oil recovery. (Journal of Mathematics Mechanics and Computer Science, 2012)
In this work research of applicability of the CUDA technology for a parallelization of three-dimensional calculations of oil production is carried out. Hydrodynamic calculations were carried out on artificially created test model and model of one of fields of the Western Kazakhstan. The algorithm of parallel calculation of the water flooding problem using CUDA technology was developed. The maximum acceleration of calculations in 60,4 times on the GPU GeForce GTX 560 was achieved.